EFEKTIVITAS PENGGUNAAN APLIKASI KAHOOT DALAM PEMBELAJARAN DI SMP SATAP 3 SOJOL UTARA - Erni Nurdin; Muh. Ikram (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2025)
This study aimed to describe the effectiveness of using the Kahoot application in learning at Satap 3 Sojol Utara Junior High School and to identify the supporting and inhibiting factors of its implementation. The study employed a qualitative approach with a descriptive research design. The research informants consisted of the principal, a Civic Education teacher, and students. Data were collected through interviews, observations, and documentation and analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the use of Kahoot in learning was effective. Its effectiveness was reflected in improved learning quality through a more interesting and interactive learning atmosphere, the suitability of question difficulty to students' abilities, increased student participation and enthusiasm, and more efficient time management. Observation results showed that students were more focused, actively answered questions, and became directly involved in the learning process. Documentation also showed that Kahoot had been incorporated into the learning plan and that the questions were adjusted to the learning materials and students' abilities. Supporting factors included student enthusiasm, school support, available facilities, ease of application use, and teachers' ability to adjust questions. Inhibiting factors included limited teacher training, unstable internet connectivity, and differences in students' abilities. Therefore, Kahoot can be utilized as an interactive learning medium to improve learning quality and student engagement.